1975
DOI: 10.1530/acta.0.0800188
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECT OF OESTRADIOL-3N-BIS-(2-CHLOROETHYL)CARBAMATE-17β-PHOSPHATE (ESTRACYT®) ON THE 5α-Reductase IN THE RAT VENTRAL PROSTATE

Abstract: The ventral prostate of the rat both after in vitro incubation and in vivo experiments was found to contain appreciable 5\g=a\-reductaseactivity, whilst a very low activity was registered in the diaphragm and liver. Neither Estracyt\s=r\ nor LEO275 (Estracyt\s=r\ without the phosphate group in position 17 of the oestradiol moiety) had an inhibitory effect on the enzyme activity after in vitro incubation but equivalent amounts of oestradiol-17\g=b\ and oestradiol-17\g=b\-phosphatesignificantly reduced 5\ g=a\ \… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The dorsolateral lobe of the rat prostate displays unique sensitivity to estrogenic action in other respects not seen in the ventral lobe. Thus, estrogen induced uptake of 65Zn by the rat dorsolateral prostate in a highly tissue-specific manner [15], Zinc is a potent inhibitor of 5a-RA, at least in nuclei of rat ventral prostate [7], Whether this relationship of estrogens, zinc and 5a-reduction is signi ficant to the mechanism of the anti-androgen action of estro gens remains to be determined. Synthetically modified steroids and steroid-cytostatic com plexes are being increasingly utilized in chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dorsolateral lobe of the rat prostate displays unique sensitivity to estrogenic action in other respects not seen in the ventral lobe. Thus, estrogen induced uptake of 65Zn by the rat dorsolateral prostate in a highly tissue-specific manner [15], Zinc is a potent inhibitor of 5a-RA, at least in nuclei of rat ventral prostate [7], Whether this relationship of estrogens, zinc and 5a-reduction is signi ficant to the mechanism of the anti-androgen action of estro gens remains to be determined. Synthetically modified steroids and steroid-cytostatic com plexes are being increasingly utilized in chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that one of the properties in its anti-androgenic action is an influence on 5 a-R A [7,8,19]. In vivo administration of estracyt to dogs and rats resulted in diminished 5a-RA of their prostates [8], H isaeter [7] reported no effect by estracyt on the rat ventral prostate after in vitro incubation or short-term (half-hour) in vivo adminis tration of the drug. Marked inhibitory effect was observed only after long-term (3 days) administration of estracyt.…”
Section: Discussionmentioning
confidence: 99%
“…Some may suppress the interstitial cell stimulating hormone with consequent reduction in testosterone secretion (Alder, Burger, Davis, Dulmanis, Hudson, Sarfaty & Straffon, 1968;Kirschner & Schneider, 1972). Other workers have also demonstrated a direct influence by these agents on the andro¬ genic activity of the prostate (Farnsworth, 1969;Albin, Vittek, Gordon, Altman, Olivo & Southren, 1973;Jenkins & McCaffery, 1974;Hoisaeter, 1975).…”
Section: Introductionmentioning
confidence: 99%